Bioalcohol production from spent coffee grounds and okara waste biomass by engineered Bacillus subtilis - Kim, Eun Joo; Seo, Dahee; Choi, Kwon Young (Biomass Conversion and Biorefinery, 2020)
Protein biomass is one of the useful biomasses which could be converted to various biochemicals. In this study, protein-rich food wastes such as SCG (spent coffee ground) and okara waste were utilized for production of bioalcohol of ethanol, isobutanol, and methylbutanols by engineered Bacillus subtilisΔcodYΔbkdBΔrelA. Protein biomass is composed of amino acids, and some are depleted in the early phase of biotransformation process. This causes cellular stress and low growth rate of host B. subtilis strains leading to low productivity of biochemicals. To overcome this nutritional stress, B. subtilis host strain was engineered to restore nutritional stress by inactivation of RelA regulatory protein with additional supplement of lysine and cysteine. Finally, the engineered B. subtilis ΔcodYΔbkdBΔrelA showed the highest bioalcohol production of 0.59 ± 0.09 g/L and 0.43 ± 0.03 g/L from SCG and okara protein resources, respectively.
Keywords: Bacillus Subtilis; Biotransformation process; Nutritional stress; Protein biomass; Regulatory protein; RelA; Spent coffee grounds; Sporulation; Bacillus subtilis; Nutritional stress; Protein conversion; Protein waste; RelA; Sporulation